Desafíos para el Ecuador en materia de remediación ambiental de la pequeña minería - Morán Lescano, Héctor Francisco (2022)
This research has a descriptive and explanatory methodology, with a mixed approach that includes: analysis of quantitative and qualitative information. In the first chapter, the objective of the research, the driving force, the background of the topic, the justification and the delimitation or scope of the research are presented. The second chapter focuses on the study of the increase of small-scale mining in Ecuador, the environmental responsibilities involved in the practice of mining exploitation, the recognition given by the State to nature as a subject of law, the policies and legal parameters related to mining, and environmental remediation as a basis for the conservation of nature, a journey is made to the beginnings of mining and how it has influenced the development of modern society, the types of mining exploitation in Ecuador, its legal framework, the rights of nature, the idea of sustainability in mining activity, the environmental impact aspects of this practice, the conceptual framework, the institutional framework of mining control, reference is made to other mining concepts such as: The importance of environmental conservation is explained and emphasis is placed on the risks arising from the uncontrolled exploitation of natural resources. Continuing with chapter three, which focuses on the application of surveys and interviews in order to know the real context of the mining situation in the country. Finally, chapter four develops a series of proposals aimed at improving the control of small mining activities in relation to compliance with environmental remediation.